Inspection and maintenance of reinforced and prestressed concrete structures (Thomas Telford, 1986)
The extent of the investment in concrete structures has emphasized the need to maintain these structures. This guide describes various types of damage, which may be discovered, and the equipment used to carry out inspections. It includes suggested inspection intervals, related to the severity of loadings and environmental conditions.
Prepared by the FIP Commission on Practical COnstruction.
Keywords: Reinforced concrete construction -- Inspection.; Prestressed concrete construction -- Inspection.; elektronické knihy; electronic books